Effect of calcitonin on bone regeneration in male rats: a histomorphometric analysis - Almeida, J. D.; Arisawa, E. A. L.; da Rocha, R. F.; Carvalho, Y. R. (Churchill Livingstone, 2007)
The aim of this study was to evaluate the effectiveness of calcitonin in promoting bone growth in surgical bone defects in rat mandibles. Fifty male rats were divided into two groups: bone defect (control) and bone defect with calcitonin (experimental). A circular bone defect 4 mm in diameter was made in the mandibular bone of the rats in the angle region, and covered with a polytetrafluoroethylene barrier. The experimental group received 2 IU/kg of synthetic salmon calcitonin intramuscularly three times a week, with treatment starting immediately after surgery. The animals were killed 3, 7, 14, 21 and 28 days after the surgical procedure. The bone defects were examined histologically and by histomorphometric analysis. The Student t-test was applied to the histomorphometric data, with the level of significance set at 5%. The animals of the experimental group showed a lower level of bone formation at almost all time points than the control group, but no difference between groups was observed 28 days after surgery. The volume of newly formed bone matrix was significantly greater in the control than the experimental group at 7, 14 and 21 days, as determined by both morphologic and histomorphometric analysis. Bone repair in the calcitonin-treated animals was delayed in comparison to controls, indicating the need for further studies on male rats.
Keywords: calcitonin; bone regeneration; mandible